Identifying risk factors for stunting among toddlers at PPA Helefanika, Gunungsitoli City - Purba, Eva Marlina; Damanik, Hosiana Rodearni; Harefa, Edward; Halawa, Alfrin (Program Studi Magister Kesehatan Masyarakat Universitas Prima Indonesia, 2024)
Stunting exerts detrimental effects on health, growth and development, and economic outcomes. These adverse impacts encompass elevated risks of morbidity and mortality, cognitive and language delays, and increased healthcare expenditures. Given these significant consequences, stunting has become a global health priority. This cross-sectional study investigates the influence of maternal height and exclusive breastfeeding practices on the incidence of stunting among children under five years of age in Gunungsitoli City. Conducted from February to April 2024, the study initially included 375 children aged 12–59 months. Due to specific inclusion criteria, the final sample comprised 63 participants selected through purposive sampling. The independent variables analyzed were maternal height and exclusive breastfeeding, with stunting incidence serving as the dependent variable. Data collection employed five questionnaires, and maternal height was measured using a stadiometer. Statistical analyses, including univariate analysis and chi-square tests, were performed using SPSS version 25.0 to explore associations between the variables. The results revealed that most mothers had an elementary school education (34.85%), exhibited normal height (63.64%), and the majority of children were exclusively breastfed (60.61%). Statistical analysis demonstrated a significant association between maternal height and stunting incidence (p=0.026), indicating that children born to shorter mothers were at higher risk of stunting. Furthermore, a significant association was found between exclusive breastfeeding practices and stunting incidence (p=0.003), with children who were not exclusively breastfed having a 3.94 times greater odds of experiencing stunting. This study concludes that maternal height and exclusive breastfeeding practices are crucial factors influencing the incidence of stunting in children.